2021
DOI: 10.1038/s42003-021-01678-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism and structural basis of small-molecule modulation of the gating of acid-sensing ion channel 1

Abstract: Acid-sensing ion channels (ASICs) are proton-gated cation channels critical for neuronal functions. Studies of ASIC1, a major ASIC isoform and proton sensor, have identified acidic pocket, an extracellular region enriched in acidic residues, as a key participant in channel gating. While binding to this region by the venom peptide psalmotoxin modulates channel gating, molecular and structural mechanisms of ASIC gating modulation by small molecules are poorly understood. Here, combining functional, crystallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 50 publications
1
19
0
2
Order By: Relevance
“…As noted elsewhere , chloride ions are found in the acidic pocket binding site of nearly all open/desensitized state solved structures but not in any resting state structure (Table 1; Baconguis et al, 2014;Baconguis & Gouaux, 2012;Dawson et al, 2012;Gonzales et al, 2009;Jasti et al, 2007;Liu et al, 2021;Sun et al, 2020;Wu et al, 2021;. Figure 1c,d shows such examples where the chloride binding site is formed in the open and desensitized states but when the α5 helix opens outward as in the resting state, the site is essentially abolished.…”
Section: Chloride Binds Exclusively To the Collapsed Conformation Of ...mentioning
confidence: 59%
“…As noted elsewhere , chloride ions are found in the acidic pocket binding site of nearly all open/desensitized state solved structures but not in any resting state structure (Table 1; Baconguis et al, 2014;Baconguis & Gouaux, 2012;Dawson et al, 2012;Gonzales et al, 2009;Jasti et al, 2007;Liu et al, 2021;Sun et al, 2020;Wu et al, 2021;. Figure 1c,d shows such examples where the chloride binding site is formed in the open and desensitized states but when the α5 helix opens outward as in the resting state, the site is essentially abolished.…”
Section: Chloride Binds Exclusively To the Collapsed Conformation Of ...mentioning
confidence: 59%
“…This fast moving technique has also recently allowed to unravel the whole apo structure of the cASIC1a channel, both in the pH = 7.0 desensitized and the pH = 8.0 resting conformations, at resolutions of ~ 2.8 and 3.7 Å, clarifying details of the way the channel works [9]. Importantly, when present work was nearly completed, two powerful small-molecule modulators of cASIC1a and rASIC1a have been presented, which, however, involve an acidic pocket different from those known for the long peptides [10].…”
Section: Introductionmentioning
confidence: 74%
“…Similar to previous work by Buta and colleagues, a recent report from Janssen Research and Development LLC (San Diego, CA) described the characterization of 5-amidino­benzimidazole and 3-aminoindazole leads inspired by PcTX1 . The authors described pH-dependent inhibition of ASIC1 activity in Chinese Hamster Ovary (CHO) cells and demonstrated that the leads occupied an allosteric binding site within the extracellular PcTX1 domain through solution of a X-ray cocrystal complex with chicken ASIC1a (Protein Data Bank ID 6X9H).…”
Section: Introductionmentioning
confidence: 77%